Transfer of a Satellite from High Elliptical to Geostationary Orbit with the Help of Electric Propulsion. (2017) - Salmin, V.V.; Petrukhina, K.V.; Kvetkin, A.A.
Abstract: This paper considers a combined scheme of insertion of a satellite into a geostationary orbit with the help of high and low torque thrusters. The start orbit is high elliptical and is formed by the third stage of the launch vehicle. Further insertion is performed by an electric propulsion unit. The trajectory of insertion, transfer time and propellant mass have been calculated.